The whispering room : a Jane Hawk novel - Koontz, Dean R. (Dean Ray), 1945- (New York, NY : Bantam Books, 2018)
"'No time to delay. Do what you were born to do. Fame will be yours when you do this.' These are the words that ring in the mind of mild-mannered, beloved schoolteacher Cora Gundersun--just before she takes her own life, and many others, in a shocking act of carnage. When the disturbing contents of her secret journal are discovered, it seems certain that she must have been insane. But Jane Hawk knows better. In the wake of her husband's inexplicable suicide--and the equally mysterious deaths of scores of other exemplary individuals--Jane picks up the trail of a secret cabal of powerful players who think themselves above the law and beyond punishment. But the ruthless people bent on hijacking America's future for their own monstrous ends never banked on a highly trained FBI agent willing to go rogue--and become the nation's most wanted fugitive--in order to derail their insidious plans to gain absolute power with a terrifying technological breakthrough. Driven by love for her lost husband and by fear for the five-year-old son she has sent into hiding, Jane Hawk has become an unstoppable predator. Those she is hunting will have nowhere to run when her shadow falls across them."--Dust jacket flap of hardcover edition.
Sequel to The Silent corner.
Includes an excerpt from The crooked staircase.
107578
Keywords: Widows -- Fiction; Fugitives from justice; Suicide; Conspiracy; Truth; Thrillers (Fiction); Psychological fiction; Suspense fiction; Psychological fiction